(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Based on performance analysis of clothing exposed to electromagnetic radiation, a electromagnetic model for abdominal cavity of human body is established using electromagnetic simulation software (Ansoft HFSS). This can be applied to simulate the specific absorption rate (SAR) of the abdominal cavity under irradiation of electromagnetic waves. The SAR of the abdominal cavity with or without protective clothing and with different clothing has been compared. The differences in electromagnetic protective performance between clothing made of these materials are also discussed. The results show that the SAR of the abdominal cavity is larger when the radiation source frequency increases over a range of 300MHz to 900MHz .While at the same frequency of radiation sources, the protective performance of different clothing materials is related to their electrical characteristic parameters and protection patterns. Also simply using the shielding effectiveness (SE) of clothing materials to illustrate the protective performance of clothing is relatively unilateral. Visualization of the electromagnetic protective performance of clothing can be preliminary achieved. The results of this research can also be applied to improve the electromagnetic protective performance of clothing in the process of design and manufacture to ensure health and safety of the people.